Verification of a fusion neutron diagnostic Bonner sphere spectrometer on measurement of a 241Am-Be neutron source - Cao, Jing; Jiang, Chun-Yu; Yang, Qing-Wei; Yin, Ze-Jie (Nuclear science and techniques, 2016)
A Bonner sphere spectrometer（BSS） was developed for neutron diagnostic on HL2A Tokamak.It contains eight polyethylene spheres embedded with SP93 He proportional counter.Before setting up on the Tokamak experimental hall,a verification experiment was arranged on a241Am–Be neutron source to test its spectrometry capability.The neutron response functions were calculated by Monte Carlo code Geant4 to simulate the real measurement environments.By least square method,the neutron spectrum was finally unfolded on log domain from0.1 e V to 11 Me V.It has a remarkable consistency to the ISO 8529-1 standard241Am–Be neutron spectrum.This shows that the BSS is effective and reliable for neutron spectrum determination.